Біоекологічні особливості бобівника трилистого (Menyanthes trifoliata L., родина Menyanthaceae) в умовах інтродукції в Узбекистан - Shoyakubov, R.S.; Arabova, N.; Matyunina, T.Y. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2001)
Flowering biology, pollination and morpho-biological peculiarities of the drug plant Menyanthes trifoliata L. have been investigated for the first time under the conditions of introduction in Uzbekistan.